Application of biomarkers in characterization of organic matter source, maturity and palaeoredox condition of black shales from the upper Permian Dalong Formation in Southern Anhui Province, South China - Ding, Jianghui; Sun, Jinsheng; Nie, Haikuan; Yang, Xiangtong; Ye, Yu; Shi, Gang; Wang, Ruyi; Huang, Bo; Li, Huili (Geological journal (Chichester, England), 2023)
The organic‐rich shale in the upper Permian Dalong Formation in Southern Anhui Province is not only regarded as a high‐quality hydrocarbon source rock, but one of the potential targets for shale oil and gas exploration in Southern China. Organic matter types in such a setting remain a subject of debate. The major point of controversy is whether they are dominated by oil‐prone types or gas‐prone types. A total of 20 rock samples collected from Gangdi‐1 well were conducted for analysis of organic geochemistry. Results show that Dalong Formation shale extracts exhibit a wide range of C12‐C35 n‐alkanes and acyclic isoprenoids. The chromatograms display an unimodal distribution with carbon peak in the range of nC18‐nC22 and low quantities of long‐chain (nC25+) n‐alkanes. Relatively high ratios of nC21‐/nC22+ and C27/C29 regular steranes demonstrate that organic matter is mainly originated from lower aquatic organisms and followed by higher plants in a local area. This is also supported by the variations of the δ13C values of C13‐C26 n‐alkanes for the target samples being in the range of 3.0‰–5.6‰ offset, which is slightly higher than the corresponding value (1.6‰) of n‐alkanes from a single source. All these pieces of information decipher that the organic matter in Dalong Formation shale may be dominated by type I and followed by type II1. Moreover, the maturity proxies according to both organic petrography (Ro and Tmax) and biomarkers such as ratios of C29 20 S/(20 S + 20R) and C29 ββ/(αα + ββ) together indicate that organic matter in Dalong Formation shale is in a mature stage of hydrocarbon generation. Furthermore, a cross‐plot of total organic carbon versus total sulphur as well as Pr/Ph ratio and Pr/nC17‐Ph/nC18 diagram elucidates that Dalong Formation shales were mainly formed in a marine reducing environment. Finally, two depositional models of organic matter enrichment are proposed. The abundant lower aquatic organisms with few terrestrial detrital inputs and the reducing water environment together promote organic matter accumulation. Dalong Formation shales were deposited in a marine reducing environment and organic matter is dominated by type I and followed by type II1 in such a setting. Two depositional models of organic matter enrichment in deep‐ and shallow‐water shelf systems are established.